Afterimages are biased by top-down information. (November 2015) - Utz, Sandra; Carbon, Claus-Christian
The afterimage illusion refers to a complementary colored image continuing to appear in the observer's vision after the exposure to the original image has ceased. It is assumed to be a phenomenon of the primary visual pathway, caused by overstimulation of photoreceptors of the retina. The aim of the present study was to investigate the nature of afterimage perceptions; mainly whether it is a mere physical, that is, low-level effect or whether it can be modulated by top-down processes, that is, high-level processes. Participants were first exposed to five either strongly female or male faces (Experiment 1), objects highly associated with female or male gender (Experiment 2) or female versus male names (Experiment 3), followed by a negativated image of a gender-neutral face which had to be fixated for 20 s to elicit an afterimage. Participants had to rate their afterimages according to sexual dimorphism, showing that the afterimage of the gender-neutral face was perceived as significantly more female in the female priming condition compared with the male priming condition, independently of the priming quality (faces, objects, and names). Our results documented, in addition to previously presumed bottom-up mechanisms, a prominent influence of top-down processing on the perception of afterimages via priming mechanisms (female primes led to more female afterimage perception).